Does 'altitude training' increase exercise performance in elite athletes?. Issue 7 (13th June 2016) - Lundby, Carsten; Robach, Paul
New Findings: What is the topic of this review? The aim is to evaluate the effectiveness of various altitude training strategies as investigated within the last few years. What advances does it highlight? Based on the available literature, the foundation to recommend altitude training to athletes is weak. Athletes may use one of the various altitude training strategies to improve exercise performance. The scientific support for such strategies is, however, not as sound as one would perhaps imagine. The question addressed in this review is whether altitude training should be recommended to elite athletes or not. Abstract :